KONTRIBUSI TIKUS PUTIH DALAM KEMAJUAN FARMAKOLOGI - Alya Salsabillah Manangin (CV. Adiba Aisha Amira, 2025)
White rats (Rattus norvegicus) are the most commonly used laboratory animals in pharmacological and toxicological research due to their physiological similarities to humans, ease of handling, and cost efficiency. This article discusses proper handling techniques for white rats as research subjects to ensure the validity of results and animal welfare. Crucial aspects reviewed include ethical standards for laboratory animal use, optimal maintenance techniques covering cage conditions, nutrition, light cycles, and temperature control, as well as handling methods that minimize stress. The discussion includes acclimatization procedures, safe restraint techniques, methods of drug administration through various routes, blood and tissue sampling techniques, and health monitoring parameters. Humane euthanasia methods in accordance with ethical protocols are also outlined. The application of the 3R principles (Replacement, Reduction, Refinement) in research design is discussed as an ethical framework that must be implemented. Understanding and applying proper handling techniques for white rats not only improves the quality and reliability of pharmacological and toxicological research data but also ensures animal welfare aspects that are the moral responsibility of researchers.